2021
DOI: 10.1093/infdis/jiab427
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diabetes and Prediabetes on Antituberculosis Treatment Outcomes: A Multicenter Prospective Cohort Study

Abstract: Background It is unclear whether diabetes or prediabetes affect unfavorable treatment outcomes and death in people with tuberculosis (PWTB). Methods Culture-confirmed drug-susceptible PWTB, enrolled in Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil between 2015-2019 (n=643) were stratified based on glycemic status according to baseline glycated hemoglobin. Unfavorable TB outcome was defined as tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
18
0
3
Order By: Relevance
“…Em países com alta carga de tuberculose, como o Brasil, há poucos estudos prospectivos nos quais se analisam as características clínicas, microbiológicas e radiográficas de pacientes com TBP ou o papel do DM e pré-DM nos desfechos do tratamento da TBP. (8,10) Em nosso estudo, a frequência de DM em pacientes com TBP (14,2%) foi maior do que a relatada em outro estudo realizado no Brasil (8) e mais próxima das relatadas em outras séries (de 12,8% a 25%), (16)(17)(18)(19) porém menor do que a relatada em um estudo realizado na Índia, (15) no qual a proporção de pacientes com tuberculose e DM foi de 30%. Em países como a China (20) e o Quênia, (21) a frequência de DMTB é menor (5,0% e 6,3%, respectivamente) do que a observada em nosso estudo.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Em países com alta carga de tuberculose, como o Brasil, há poucos estudos prospectivos nos quais se analisam as características clínicas, microbiológicas e radiográficas de pacientes com TBP ou o papel do DM e pré-DM nos desfechos do tratamento da TBP. (8,10) Em nosso estudo, a frequência de DM em pacientes com TBP (14,2%) foi maior do que a relatada em outro estudo realizado no Brasil (8) e mais próxima das relatadas em outras séries (de 12,8% a 25%), (16)(17)(18)(19) porém menor do que a relatada em um estudo realizado na Índia, (15) no qual a proporção de pacientes com tuberculose e DM foi de 30%. Em países como a China (20) e o Quênia, (21) a frequência de DMTB é menor (5,0% e 6,3%, respectivamente) do que a observada em nosso estudo.…”
Section: Discussionunclassified
“…Em nosso estudo, o pré-DM foi identificado em 47,1% dos pacientes com tuberculose, valor superior ao descrito em outros estudos, com prevalência de 7,4% a 37,5%. (8,16,17,(19)(20)(21) No entanto, observamos uma redução significativa dos níveis de HbA1c no segundo mês de tratamento. A normalização dos níveis glicêmicos durante o tratamento da tuberculose em pacientes inicialmente disglicêmicos também foi relatada por outros autores.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…T2DM is significantly associated with adverse TB treatment outcomes and mortality ( 42 , 44 ). In addition, T2DM is associated with early mortality during TB treatment (adjusted hazard ratio: 4.36; 95% confidence interval: 1.62–11.76) ( 48 ), and more than a 2- fold increased risk of death (2.16 times) ( 49 ).…”
Section: Epidemiological Effects Of T2dm On Tbmentioning
confidence: 99%
“…A recent prospective study following more than 700 individuals from West India showed that T2D significantly increased the risk of early mortality during TB treatment (aHR, 4.36; 95% CI, 1.62-11.76) [31]. A multi-center prospective cohort study from Brazil demonstrated that participants with diabetes but not prediabetes are at higher risk of having an unfavourable outcome (1.76 and 2.45 times separately from two different cohorts) and an increased risk of death (1.93 and 2.16 times) [32].…”
Section: T2d Increases Tb Disease Severity and The Risk Of Adverse Tb Treatment Outcomesmentioning
confidence: 99%